Increased Mortality Trends in Patients With Chronic Non-communicable Diseases and Comorbid Hypertension in the United States, 2000–2019 - Ouyang, Feiyun; Cheng, Xunjie; Zhou, Wei; He, Jun; Xiao, Shuiyuan (Frontiers in Public Health, 2022)
Background According to the Sustainable Development Goals (SDGs), countries are required to reduce the mortality rates of four main non-communicable diseases (NCDs), including cardiovascular diseases (CVDs), diabetes mellitus (DM), chronic respiratory diseases (CRDs), and cancer (CA), by one-third in 2030 from the 2015 level. However, progress fell short of expectations, partly attributed to the high rates of hypertension-related NCD mortality. This study aimed to investigate the mortality trends of SDG-targeted NCDs with comorbid hypertension. In addition, the disparities in mortality rates among different demographic subgroups were further explored. Methods Mortality data from 2000 to 2019 were acquired from the Centers for Disease Control and Prevention in the United States. SDG-targeted NCDs were considered the underlying causes of death, and hypertension was considered a multiple cause of death. Permutation tests were performed to determine the time points of Joinpoints for mortality trends. The annual percent changes and average annual percent changes (AAPCs), as well as 95% confidence intervals (CIs), were calculated to demonstrate the temporary trend of mortality rates overall and by age, sex, ethnicity, and region. Results The hypertension-related DM, CRD, and CA mortality rates increased over the 20 years, of which the AAPCs were 2.0% (95% CI: 1.4%, 2.6%), 3.2% (95% CI: 2.8%, 3.6%), and 2.1% (95% CI: 1.6%, 2.6%), respectively. Moreover, despite decreasing between 2005 and 2015, the hypertension-related CVD mortality rate increased from 2015 to 2019 [APC: 1.3% (95% CI: 0.7%, 1.9%)]. The increased trends were consistent across most age groups. Mortality rates among men were higher and increased faster than those among women. The hypertension-related CVD, DM, and CA mortality rates among African American people were higher than those among White people. The increased mortality rates in rural areas, especially in rural south, were higher than those in urban areas. Conclusion In the United States, the hypertension-related DM, CRD, and CA mortality rates increased between 2000 and 2019, as well as hypertension-related CVD mortality between 2015 and 2019. Disparities existed among different sexes, ethnicities, and areas. Actions to prevent and manage hypertension among patients with NCDs are required to reduce the high mortality rates and minimize disparities.